PPARγ Agonists: Blood Pressure and Edema - Bonnie L. Blazer-Yost (PPAR Research)
Peroxisome proliferator activated receptor γ (PPARγ) agonists are widely used in the treatment of type 2 diabetes. Side effects of drug treatment include both fluid retention and a lowering of blood pressure. Data from animal and human studies suggest that these effects arise, at least in part, from drug-induced changes in the kidney. In order to capitalize on the positive aspect (lowering of blood pressure) and exclude the negative one (fluid retention), it is necessary to understand the mechanisms of action underlying each of the effects. When interpreted with known physiological principles, current hypotheses regarding potential mechanisms produce enigmas that are difficult to resolve. This paper is a summary of the current understanding of PPARγ agonist effects on both blood pressure and fluid retention from a renal perspective and concludes with the newest studies that suggest alternative pathways within the kidney that could contribute to the observed drug-induced effects.